2009
DOI: 10.1093/fampra/cmp048
|View full text |Cite
|
Sign up to set email alerts
|

Waist circumference measurement: knowledge, attitudes and barriers in patients and practitioners in a multi-ethnic population

Abstract: This study adds to our understanding of views on WCM in a multi-ethnic setting, highlighting factors for consideration if WCM is to be facilitated in routine practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 18 publications
5
60
0
Order By: Relevance
“…In contrast, despite evidence that waistline is a strong predictor of cardiovascular related morbidity and mortality and has been recommended since 1998 [46], only one in ten patients had a measure done [47,48]. Low levels of uptake have also been documented in other countries [49,50]. One study reported that family physicians cited lack of time, extra workload, opportunity costs, and concerns about the acceptability of this manoeuvre as barriers to uptake [50].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, despite evidence that waistline is a strong predictor of cardiovascular related morbidity and mortality and has been recommended since 1998 [46], only one in ten patients had a measure done [47,48]. Low levels of uptake have also been documented in other countries [49,50]. One study reported that family physicians cited lack of time, extra workload, opportunity costs, and concerns about the acceptability of this manoeuvre as barriers to uptake [50].…”
Section: Discussionmentioning
confidence: 99%
“…BMI is a simple and widely used clinical measure; however, BMI may not be a reliable indicator of health risk across all racial and ethnic groups (6,8,9). This may be due, at least in part, to errors inherent in the use of self-report measures of BMI (6).…”
Section: Introductionmentioning
confidence: 99%
“…This may be due, at least in part, to errors inherent in the use of self-report measures of BMI (6). Considerable attention has been given to waist circumference as a complementary (10) and, in some cases, superior (8) assessment to BMI.…”
Section: Introductionmentioning
confidence: 99%
“…5, 6 Waist circumference (WC) and waist-to-hip ratio (WHR), measures of central adiposity, are stronger predictors of cardiovascular risk compared to BMI, yet are infrequently quantified in the clinical setting. 7 Central adiposity is linked to adverse metabolic profiles and greater systemic inflammation, both potent risk factors for the development of cardiovascular disease. 8 Previous analyses have shown an independent association between measures of central obesity and left ventricular (LV) dysfunction, particularly diastolic dysfunction.…”
mentioning
confidence: 99%